Yes We Cannibal Panel Discussion: Reading, Unearthing, and Eating Anthropocentrism with Cesar & Lois - Keel, Mat (Anthropology of consciousness, 2022)
This panel discussion took place on June 26, 2021, as part of the programming for an exhibition by critical art collaborative Cesar & Lois at experimental art and research project space Yes We Cannibal (Baton Rouge, LA). The exhibition was entitled Eat the Anthropocene with Cesar & Lois, mycelia and friend entities and ran for six weeks. The panel discussion collected scholars from art, anthropology, literature, landscape architecture, and amateur Mycology to elucidate themes relevant to the artwork, which features a variety of experimental collaborations between codices and fungal life.